2014
DOI: 10.1016/j.ijsu.2013.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone treatment against acetaminophen-induced hepatotoxicity in rats

Abstract: TQ treatment may have an important therapeuthic effect via the upregulation of antioxidant systems in the APAP-induced liver hepatotoxicity in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
57
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 32 publications
9
57
1
Order By: Relevance
“…[9] The protective effects of TQ on the kidney and liver, observed in the two models of the present study, may be explained, at least in part, by the antioxidant property of TQ and its ability to: (1) scavenge free radicals, (2) protect cellular membranes against lipid peroxide attack, (3) preserve intracellular GSH and (4) increase the expression of tissue antioxidant genes. [10,11,17] Besides its free radical scavenging and antilipoperoxidative effects, it is likely that other actions of TQ, for example inhibition of cyclooxygenase-dependent production of some inflammatory mediators, [32] improvement of mitochondrial function and enhancing ATP production [12] might be involved in its nephroprotective and hepatoprotective effects against oxidative tissue damage observed after CsA treatment and acute renal I/R.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] The protective effects of TQ on the kidney and liver, observed in the two models of the present study, may be explained, at least in part, by the antioxidant property of TQ and its ability to: (1) scavenge free radicals, (2) protect cellular membranes against lipid peroxide attack, (3) preserve intracellular GSH and (4) increase the expression of tissue antioxidant genes. [10,11,17] Besides its free radical scavenging and antilipoperoxidative effects, it is likely that other actions of TQ, for example inhibition of cyclooxygenase-dependent production of some inflammatory mediators, [32] improvement of mitochondrial function and enhancing ATP production [12] might be involved in its nephroprotective and hepatoprotective effects against oxidative tissue damage observed after CsA treatment and acute renal I/R.…”
Section: Discussionmentioning
confidence: 99%
“…The seeds and oil are used as food supplements and in folk medicine for a number of conditions that include asthma, hypertension and diabetes. [10] Previous studies, using different experimental models, have shown that TQ exerts protective effects against free radical-induced oxidative damage in several tissues as in acetaminophen-induced hepatotoxicity, [11] cyclophosphamide-induced cardiotoxicity [12] and anti-tuberculosis drugs-induced liver damage. [13] All of these studies have demonstrated that TQ not only scavenges free radicals, but also inhibits lipid peroxidation through its antioxidant effect.…”
Section: Introductionmentioning
confidence: 99%
“…APAP control group was a fed normal diet for 3 weeks, and it received APAP (500 mg/kg, PO) prepared in 1% Tween 80 on the last day of the experiment. [ 22 ]…”
Section: Methodsmentioning
confidence: 99%
“…TQ is known to possess strong antioxidant and anti-inflammatory properties. [31][32][33] As TQ has been previously found to be beneficial in several experimental models in which oxidative and inflammatory tissue injuries are the basis of toxicity, 19,25,34,35 and as it is present in the oil of the commonly available black seed, a safe natural product, it was therefore of interest to test here if this compound has a possible ameliorative action against the combined toxicity of CP and DEP. As far as we are aware, this has not been reported before.…”
Section: Introductionmentioning
confidence: 99%